Informal Entrepreneurship Education: Overview of the Russian Field - Pavel Sorokin; Aleksandr Povalko; Iuliia Vyatskya (Foresight and STI Governance)
This article analyzes the informal sector of entrepreneurial education — free “open” educational projects at the federal level in the context of broader trends in the development of education and society, including education’s ‘unbundling’. The search for information was carried out using the Internet, as a result 45 initiatives were discovered. The results show that the sector of entrepreneurship education is broad, but there are a large number of areas for improvement, in which universities can play an important role. In particular, this concerns elaborating and implementing a system for evaluating educational results, organizing monitoring of the effectiveness of such initiatives, including the analysis of success stories. In addition, a separate task is to expand the set of targeted programs for specific audiences (for example, unemployed), as well as to improve the content of such initiatives more deeply according to the specifics of the relevant target groups (for example, young mothers or older people).